HEllenic Registry on Myocarditis SyndromES on behalf of Hellenic Heart Failure Association: The HERMES‐HF Registry. (16th September 2020) - Adamopoulos, Stamatis; Miliopoulos, Dimitrios; Karavidas, Apostolis; Nikolaou, Maria; Lazaros, George; Gkouziouta, Angeliki; Manginas, Athanassios; Sevastos, George; Karvounis, Haralambos; Karamitsos, Theodoros D.; Hahalis, George; Leopoulou, Marianna; et al.
Abstract: Aims: Despite the existence of many studies, there are still limited data about the characteristics of myocarditis in Greece. This led to the creation of the Greek Myocarditis Registry aiming to document the different symptoms and treatment of myocarditis, assess possible prognostic factors, and find similarities and differences to what is already published in literature. This paper is a preliminary descriptive analysis of this Registry. Methods and results: We analysed data for the hospitalization period of all patients included in the Registry from December 2015 until November 2017. Statistics are reported as frequency (%) or median and inter‐quartile range (IQR) as appropriate. In total, 146 patients were included; 83.3% of the patients reported an infection during the last 3 months. The most common symptom, regardless of the underlying infection, was chest pain (82.2%) followed by dyspnoea (18.5%), while the most common finding in clinical examination was tachycardia (26.7%). Presentation was more frequent in the winter months. ECG findings were not specific, with the repolarization abnormalities being the most frequent (60.3%). Atrial fibrillation was observed in two patients, both of whom presented with a reduced ventricular systolic function. Left ventricular ejection fraction changed significantly during the hospitalization [55% (IQR: 50–60%) on admission vs. 60% (IQR: 55–60%) on discharge, P  = 0.0026]. Cardiac magnetic resonance was performed in 88 patients (61%), revealing mainly subepicardial and midcardial involvement of the lateral wall. Late gadolinium enhancement was present in all patients, while oedema was found in 39 of them. Only 11 patients underwent endomyocardial biopsy. Discharge medication consisted mainly of beta‐blockers (71.9%) and angiotensin‐converting enzyme inhibitors (41.8%), while 39.7% of the patients were prescribed both. Conclusions: This preliminary analysis describes the typical presentation of myocarditis patients in Greece. It is a first step in developing a better prognostic model for the course of the disease, which will be completed after the incorporation of the patients' follow‐up data.